Effect of metabolic syndrome and aging on Ca(2+) dysfunction in coronary smooth muscle and coronary artery disease severity in Ossabaw miniature swine - Badin, Jill K. (Exp Gerontol, 2018)
BACKGROUND: Metabolic syndrome (MetS) and aging are prevalent risk factors for coronary artery disease (CAD) and contribute to the etiology of CAD, including dysregulation of Ca(2+) handling mechanisms in coronary smooth muscle (CSM). The current study tested the hypothesis that CAD severity and CSM Ca(2+) dysregulation were different in MetS- compared to aging-induced CAD. METHODS: Young (2.5 ± 0.2 years) and old (8.8 ± 1.2 years) Ossabaw miniature swine were fed an atherogenic diet for 11 months to induce MetS and were compared to lean age-matched controls. The metabolic profile was confirmed by body weight, plasma cholesterol and triglycerides, and intravenous glucose tolerance test. CAD was measured with intravascular ultrasound (IVUS) and histology. Intracellular Ca(2+) ([Ca(2+])(i)) was assessed with fura-2 imaging. RESULTS: CAD severity was similar between MetS young and lean old swine, with MetS old swine exhibiting the most severe CAD. Compared to CSM [Ca(2+)](i) handling in lean young, the MetS young and lean old swine had increased sarcoplasmic reticulum Ca(2+) store release. MetS young swine exhibited increased Ca(2+) influx through voltage-gated Ca(2+) channels. Lean old swine exhibited attenuated sarco-endoplasmic reticulum Ca(2+) ATPase activity. MetS old and MetS young swine had similar Ca(2+) dysregulation. CONCLUSIONS: Ca(2+) dysregulation, mainly the SR Ca(2+) store, in CSM is more pronounced in lean old compared to both MetS groups, which is indicative of mild, proliferative CAD. MetS old and MetS young swine exhibit Ca(2+) dysfunction that is typical of late, severe disease. The more advanced, complex plaques in MetS old swine suggest that the “aging milieu” potentiates effects of Ca(2+) handling dysfunction in CAD.